The molecular biogeography of the Indo‐Pacific: Testing hypotheses with multispecies genetic patterns. Issue 7 (22nd April 2019) - Crandall, Eric D.; Riginos, Cynthia; Bird, Chris E.; Liggins, Libby; Treml, Eric; Beger, Maria; Barber, Paul H.; Connolly, Sean R.; Cowman, Peter F.; DiBattista, Joseph D.; Eble, Jeff A.; Magnuson, Sharon F.; et al.
Abstract: Aim: To test hypothesized biogeographic partitions of the tropical Indo‐Pacific Ocean with phylogeographic data from 56 taxa, and to evaluate the strength and nature of barriers emerging from this test. Location: The Indo‐Pacific Ocean. Time period: Pliocene through the Holocene. Major taxa studied: Fifty‐six marine species. Methods: We tested eight biogeographic hypotheses for partitioning of the Indo‐Pacific using a novel modification to analysis of molecular variance. Putative barriers to gene flow emerging from this analysis were evaluated for pairwise ΦST, and these ΦST distributions were compared to distributions from randomized datasets and simple coalescent simulations of vicariance arising from the Last Glacial Maximum. We then weighed the relative contribution of distance versus environmental or geographic barriers to pairwise ΦST with a distance‐based redundancy analysis (dbRDA). Results: We observed a diversity of outcomes, although the majority of species fit a few broad biogeographic regions. Repeated coalescent simulation of a simple vicariance model yielded a wide distribution of pairwise ΦST that was very similar to empirical distributions observed across five putative barriers to gene flow. Three of these barriers had median ΦST that were significantly larger than random expectation. Only 21 of 52 species analysed with dbRDA rejected the null model. Among these, 15 had overwater distance as a significant predictor of pairwise ΦST, while 11 were significant for geographic or environmental barriers other than distance. Main conclusions: Although there is support for three previously described barriers, phylogeographic discordance in the Indo‐Pacific Ocean indicates incongruity between processes shaping the distributions of diversity at the species and population levels. Among the many possible causes of this incongruity, genetic drift provides the most compelling explanation: given massive effective population sizes of Indo‐Pacific species, even hard vicariance for tens of thousands of years can yield ΦST values that range from 0 to nearly 0.5.